2009
DOI: 10.1590/s0101-60832009000500006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação diagnóstica de crianças e adolescentes em situação de vulnerabilidade e risco social: transtorno de conduta, transtornos de comunicação ou "transtornos do ambiente"?

Abstract: Ao se iniciar as avaliações diagnósticas e os atendimentos multidisciplinares de crianças e adolescentes em situação de risco e vulnerabilidade social (dos quais, usuários de drogas e vítimas de abuso físico e sexual), atendidos pelo Programa Equilíbrio, os profissionais envolvidos, dentre eles psiquiatras, pediatra, psicólogos, terapeutas ocupacionais, assistentes sociais, psicopedagogos, fisioterapeuta, perceberam que uma série de adaptações deveria ser feita para realizar a abordagem e a anamnese dessa popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
3
1
4
Order By: Relevance
“…Thus, one must consider that this type of behavior and expression, both physical and verbal, is part of the interaction process of these children with the world around them and that it has its role. 42 There was no difference between genders for voice alterations, which differs from other studies that indicated a prevalence of voice disorders in boys. 22---24,43,44 Researchers highlight that the behavior of boys is more impulsive and aggressive than that of girls, who more typically exhibit hyperactivity, anxiety, and leadership; the male behaviour when translated to the phonation mechanisms results in vocal abuse.…”
Section: Discussioncontrasting
confidence: 91%
“…Thus, one must consider that this type of behavior and expression, both physical and verbal, is part of the interaction process of these children with the world around them and that it has its role. 42 There was no difference between genders for voice alterations, which differs from other studies that indicated a prevalence of voice disorders in boys. 22---24,43,44 Researchers highlight that the behavior of boys is more impulsive and aggressive than that of girls, who more typically exhibit hyperactivity, anxiety, and leadership; the male behaviour when translated to the phonation mechanisms results in vocal abuse.…”
Section: Discussioncontrasting
confidence: 91%
“…Understanding any aggressive and challenging behavior as a BP, as put in the speeches of these professionals, can make children and adolescents adapted to violent environments, such as street children or communities with high rates of violence, be reduced to children with disabilities. psychopathology (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Com base nessas pesquisas, os profissionais da área da saúde terão melhores condições para formular e adaptar estratégias de prevenção, tratamento e promoção de fatores de resiliência para essa população específica, em virtude das peculiaridades do processo de avaliação e atendimento, que devem ser tratadas com cautela 72 . Sabese que quanto mais precoces as intervenções realizadas em crianças e adolescentes, melhor o prognóstico 73 .…”
Section: Limitações Metodológicas E Perspectivas Para Novos Estudosunclassified